Abiotic Stress in Plants - Fahad, Shah; Saud, Shah; Chen, Yajun; Wu, Chao; Wang, Depeng (IntechOpen, 2021)
Environmental insults such as extremes of temperature, extremes of water status, and deteriorating soil conditions pose major threats to agriculture and food security. Employing contemporary tools and techniques from all branches of science, attempts are being made worldwide to understand how plants respond to abiotic stresses with the aim to manipulate plant performance that is better suited to withstand these stresses. This book searches for possible answers to several basic questions related to plant responses towards abiotic stresses. Synthesizing developments in plant stress biology, the book offers strategies that can be used in breeding, including genomic, molecular, physiological, and biotechnological approaches that have the potential to develop resilient plants and improve crop productivity worldwide.